2020
DOI: 10.3390/cells9081806
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Analysis Reveals Production of Circular RNAs from Non-Coding Sequences

Abstract: The sequencing of total RNA depleted for ribosomal sequences remains the method of choice for the study of circRNAs. Our objective was to characterize non-canonical circRNAs, namely not originating from back splicing and circRNA produced by non-coding genes. To this end, we analyzed a dataset from porcine testis known to contain about 100 intron-derived circRNAs. Labelling reads containing a circular junction and originating from back splicing provided information on the very small contribution of long non-cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 46 publications
3
50
2
1
Order By: Relevance
“…We greatly appreciated to note [ 24 ] that CIRCexplorer2 [ 34 ] considers two models of circRNA (exonic and lariat-derived intronic). In addition to tools developed to detect “all circRNAs”, we would like to mention a tool designed to work on intronic reads [ 35 ] and the development of a dedicated approach to characterize intron-derived circRNAs [ 20 , 21 ]. In 2013, Zhang et al [ 6 ] developed circFinder specifically to study circRNAs derived from introns.…”
Section: What Can We Expect From Tools Dedicated To the Detection mentioning
confidence: 99%
See 4 more Smart Citations
“…We greatly appreciated to note [ 24 ] that CIRCexplorer2 [ 34 ] considers two models of circRNA (exonic and lariat-derived intronic). In addition to tools developed to detect “all circRNAs”, we would like to mention a tool designed to work on intronic reads [ 35 ] and the development of a dedicated approach to characterize intron-derived circRNAs [ 20 , 21 ]. In 2013, Zhang et al [ 6 ] developed circFinder specifically to study circRNAs derived from introns.…”
Section: What Can We Expect From Tools Dedicated To the Detection mentioning
confidence: 99%
“…(2) Talhouarne and Gall proposed lists of intron-derived circRNAs, particularly from mouse and human red blood cells [ 23 ]. (3) CircRNAs deriving from intron lariats were identified by our group when analyzing datasets of porcine pubertal testes [ 20 , 21 ]. (4) A recent study of neuronal cells (neuronal projections and synapses) in mice identified 278 introns as able to produce sisRNA, and reads containing circular junctions were detected in 14 of them [ 22 ].…”
Section: Review Of Reported Lariat-derived Circrna To Underline Fementioning
confidence: 99%
See 3 more Smart Citations